HIV among the street dwellers of Medellín - Alejandra Agudelo; Liliana P. Montoya; Angela Segura; Dedsy Y. Berbesi (Universidad de Antioquia, 2012)
Objective: to determine the prevalence of HIV among the street dwellers of the city of Medellin (Colombia) as well as their socio-demographic characteristics in order to deepen the understanding of the problems faced by this vulnerable group. Methodology: a cross-sectional study was conducted in which HIV seroprevalence and risk behaviors were determined. Data was processed using the SPSS 8.0 software, and the bivariate analysis was conducted using statistical methods. Results: a survey was conducted on 230 street dwellers, 69.6% of which were men. The average age was 38 ± 10.9 years, and HIV prevalence was 7.8%. This prevalence was 10% for men and 2.9% for women. The rate of infected individuals was 12% for those aged 25 to 34, 11% for individuals aged 55, and 8% for those aged 18 to 24. Additionally, 41% of men and 30% of women had correct beliefs regarding HIV transmission. Discussion: the prevalence value of 7.8%, shows that HIV infections in Colombia are concentrated in populations in a state of exclusion, stigma, and discrimination. This value also shows a need for actions targeting vulnerable groups.